Genome-Wide Transcriptional Profiling Reveals Two Distinct Outcomes in Central Nervous System Infections of Rabies Virus - Zhang, Daiting; He, Feilong; Bi, Shuilian; Guo, Huixia; Zhang, Baoshi; Wu, Fan; Liang, Jiaqi; Yang, Youtian; Tian, Qin; Ju, Chunmei; Fan, Huiying; Chen, Jinding; et al. (Frontiers in Microbiology, 2016)
Rabies remains a major public health concern in many developing countries. The precise neuropathogenesis of rabies is unknown, though it is hypothesized to be due to neuronal death or dysfunction. Mice that received intranasal inoculation of an attenuated rabies virus (RABV) strain HEP-Flury exhibited subtle clinical signs, and eventually recovered, which is different from the fatal encephalitis caused by the virulent RABV strain CVS-11. To understand the neuropathogenesis of rabies and the mechanisms of viral clearance, we applied RNA sequencing (RNA-Seq) to compare the brain transcriptomes of normal mice versus HEP-Flury or CVS-11 intranasally inoculated mice. Our results revealed that both RABV strains altered positively and negatively the expression levels of many host genes, including genes associated with innate and adaptive immunity, inflammation and cell death. It is found that HEP-Flury infection can activate the innate immunity earlier through the RIG-I/MDA-5 signaling, and the innate immunity pre-activated by HEP-Flury or Newcastle disease virus (NDV) infection can effectively prevent the CVS-11 to invade central nervous system (CNS), but fails to clear the CVS-11 after its entry into the CNS. In addition, following CVS-11 infection, genes implicated in cell adhesion, blood vessel morphogenesis and coagulation were mainly up-regulated, while the genes involved in synaptic transmission and ion transport were significantly down-regulated. On the other hand, several genes involved in the MHC class II-mediated antigen presentation pathway were activated to a greater extent after the HEP-Flury infection as compared with the CVS-11 infection suggesting that the collaboration of CD4+ T cells and MHC class II-mediated antigen presentation is critical for the clearance of attenuated RABV from the CNS. The differentially regulated genes reported here are likely to include potential therapeutic targets for expanding the postexposure treatment window for RABV infection.